المقارنة بين الموسعات القصبية (مشابهات بيتا) عن طريق الإرذاذ والبخاخ مع الحجرة الإنشاقية في علاج نوبة الربو الحادة عند الأطفال - ديب, غزل; الحكيم, أمل; الشرع, ميلاد (Latakia University Journal -Medical Sciences Series, 2019)
لقد شملت الدراسة (150) مريضا من مراجعي قسم إسعاف الأطفال في مشفى الأسد الجامعي في اللاذقية خلال عام واحد (2003-2004) بشكوى نوبة ربوية حادة (وزيز متكرر) (لقد تم استثناء النوبة الأولى والنوبة الربوية الشديدة)، وبمجال أعمار يتراوح بين 4-14 سنة . - تم ملاحظة سيطرة الذكور لدى المراجعين حيث كانت نسبة الذكور إلى الإناث هي1:2 . لقد قمنا بتقييم شدة النوبة الربوية بالاعتماد على المشعرات السريرية (عدد مرات التنفس ،علامات الشدة التنفسية ، شدة الوزيز) قياس الاكسجة النبضي ، معدل الجريان الزفيري الأعظمي (PEF) عند المرضى المتعاونين . وقمنا بتطبيق مشابهات بيتا (الالبوتيرول) بطريقتين : البخاخ مع حجرة إنشاقية (70 مريض (46%))، الارذاذ (80 مريض (54%)) وقمنا بمقارنة النتائج : * 85 مريضا من مجمل المرضى استجابوا للعلاج وخرجوا إلى المنزل. * 65 مريضا (44%) استمر لديهم وجود الأعراض بعد العلاج فتم إعطاؤهم الستيروئيدات بشكل وريدي وفي بعض الحالات احتاج المرضى إلى جلسات إضافية أو أدرينالين تحت الجلد. ،وتم إجراء صورة صدر في 7 حالات كانت طبيعية في 5 منها وبينت وجود ذات رئة في حالتين وتم قبول مريض واحد في المشفى . * ولدى تحليل النتائج قمنا بتقسيم المرضى إلى مجموعات : 1- حسب معايير التقييم: مجموعة أولى اعتمدنا في تقييمها على (PEF) بالإضافة للمعايير السريرية ،مجموعة ثانية اعتمدنا في التقييم على المعايير السريرية فقط (بهدف المقارنة عند اعتماد معايير موضوعية أو شخصية وإثبات عدم وجود أي اختلاف سواء عند وجود معايير موضوعية في التقييم (PEF) أو معايير سريرية فقط قد تخضع لعوامل شخصية) . 2- حسب شدة النوبة الربوية: مجموعة أولى (نوبة خفيفة) مجموعة ثانية (نوبة متوسطة) وتبين عدم وجود أي اختلاف بين الطريقتين في علاج النوبة حسب شدتها . - ولدى تحليل نتائج المرضى الذين لم يستجيبوا قمنا بدراسة دور كل من (القصة العائلية ، الأمراض التأتبية المرافقة لدى نفس المريض ، التدخين السلبي ، الرطوبة في المنزل) ولقد وجدنا أن لها جميعا دورا مهما في عدم الاستجابة للعلاج مع كون القصة العائلية والتدخين السلبي هما الأهم . The study included 150 patient who visited emergency room in pediatrics department in AL-ASSAD university hospital in Lattakia in one year (2003-2004) with asthma attack (recurrent wheezing) (we excluded first episode, and severe attacks) with age ranging between 4-14 years. - We noticed male predominance with male to female ratio 2:1. - We dpended in the assessment of the attack severity on clinical parameters (Respiratory rate, respiratory distress, wheezing severity) pulse oxymeter, and measurement of peak expiratory flow rate (PEFR) if possible. We applied β-agonist (albuterol) in two ways: MDIplus spacer (70 patients 46%), and nebulisation (80 patients 54%) for relieving the asthma attack and compared the results. 85 patients of the total number improved after 3 doses of β-agonist and were discharged. 65 patients (44%) have symptoms after 3 doses of β- agonist and they received intravenous steroid and rarely another dose of β-agonist, and chest x-ray was performed on 7 patients and it was normal in 5 and 2 patients who have pneumonia and one patient was admitted to hospital. In analyzing the results we divided the patients into two groups by assessment parameters (PEF plus clinical parameters and clinical parameters only)( for comparison between objective parameters and subjective (clinical) parameters, and we divided the patients according to the severity of the attack into two groups (mild attack, moderate attack ), and we studied the efficacy of areatment in each group, and compared them, and we found no difference between the two ways in all groups. In patients who did not respond to treatment we studied the role of (other atopic diseases in the same patient, familial history of asthma, passive smoking, humid house ,previous admission to hospital because of asthma, and we found that all of them had significant role in unresponsiveness to treatment, with the familial history of asthma and passive smoking the most important .